Thermodynamic functions of quantum electron gas in strongly anisotropic materials - Tovstyuk, C.C. (Functional Materials, 2016)
In this paper we investigate thermodynamic functions of quantum electron gas in strongly anisotropic materials and compare them with the same functions obtained for isotropic material with quadratic dependence of energy on momentum. Our results are in a good agreement with theoretical conclusions of other authors and they help to explain a number of known experimental data obtained for these materials.